Islamic Mentoring: Implementation and Impact of Mentoring Activities at Muhammadiyah 1 Junior High School Yogyakarta - Fildzah, Azmatun; Anisa Dwi Makrufi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2024)
This study examines the implementation and impact of Islamic mentoring activities on Muhammadiyah 1 Junior High School (SMP) Yogyakarta students. Mentoring activities align with the school's vision, which aims to form a generation of qualified Muslims who are superior in achievement, knowledgeable in science and technology, and environmentally cultured. This research method uses field research with a phenomenological approach and qualitative methods. The data sources came from respondents involving several school stakeholders and data collection techniques using interviews, observations, and documentation. Data credibility is strengthened through triangulation of data sources, methods, and reference materials. The data analysis follows the interactive model of Miles, Huberman, and Saldana, including data condensation, data display, and conclusion drawing. The results of the study show that the implementation of activities is carried out through school mentoring programs, namely, Dhuha Prayer Habituation Movement & Islamic Materials, Women's Training, Weekend Boarding Activity, Al-Qur'anization, and Student Cult. The impact of mentoring activities on students includes emotional, behavioral/moral, and academic improvements. This study provides a better understanding of the impact of Islamic mentoring activities